ON FAUNOGENESIS OF TENEBRIONID BEETLES (COLEOPTERA: TENEBRIONIDAE) OF MIDDLE ASIA - G. M. Abdurakhmanov; M. V. Nabozhenko (Юг России: экология, развитие, 2016)
Aim. The critic analyses of works about faunogenesis of tenebrionid beetles of Middle Asia considering the new data about phylogeography of some Mediterranean Tenebrioidae; analyses of causes of disjunction in distribution of some darkling beetles.Methods. We used important published from 1965 to 2015 works on tenebrionid faunogenesis of Middle Asia and Mediterranean and partly author’s and colleague’s material for the critic analyses.Conclusions. The hypothesis about ancient centers of origin of tenebrionid fauna of Middle Asia on coasts of Tethys Sea is confirmed by modern phylogeographic studies, but the time of the origin of recent taxa is possibly much earlier than previously assumed Pliocene-Pleistocene. New data on distribution of two species of the tribe Helopini, Eustenomacidius laevicollis and Catomus niger (the first record for Turkmenistan), which were previously known only from Tien Shan and Hissar Darvaz Mts are given. Small populations of these two species were found in the Eastern Caspian Region. We assume that the disjunction of its ranges is related with environmental factors (reduction of food resources, competition from close species), but not with geographic isolation.